From glycals to aminosugars: a challenging test for new stereoselective aminohydroxylation and related methodologies. Issue 23 (17th May 2016) - Mirabella, S.; Cardona, F.; Goti, A.
Abstract : The most relevant methods to access 1-, 2-, 3-amino or 1, 2-diaminosugars starting from unsaturated carbohydrates are concisely reviewed; the given examples illustrate the great challenges offered to several stereoselective strategies. Abstract : The introduction of amino functionalities in a regio- and stereoselective manner onto sugar scaffolds represents a great challenge in carbohydrate synthesis. The most relevant methods to access 1-, 2-, 3-amino or 1, 2-diaminosugars starting from glycals and 2, 3-hexenopyranosides derived from them are concisely reviewed. The main synthetic strategies for accessing this class of compounds are classified in intermolecular and intramolecular approaches and the key features of each class are discussed. This review highlights how carbohydrate derivatives always pose great challenges representing a benchmark for assessing the efficiency of stereoselective strategies, and aims to give the readers inspiration for the development of new procedures.